Synergistic Effects of Microbial-Induced Carbonate Precipitation and Modified Biochar on the Engineering Properties of Loess - Qibo Yan; Lingwei Kong; Shiyue Fang (Crystals)
Collapsible loess poses significant geotechnical risks due to its metastable structure and water sensitivity, while conventional stabilization methods often lack sustainability. This study investigates the synergistic effects of microbial-induced carbonate precipitation (MICP) and modified biochar (MBC) to enhance loess engineering properties. Controlled experiments evaluated hydraulic conductivity, shear strength, and stress-strress–strain behavior under varying MBC content (0–8%), cementation reagent concentration (0.5–1.5 mol/L), and confining pressures (50–400 kPa), and complemented by microstructural characterization via scanning electron microscope (SEM). Results demonstrate that MBC (4–6%) optimizes calcium carbonate distribution by providing nucleation sites, reducing hydraulic conductivity by 72% and increasing shear strength by 52% when compared with untreated loess. Elevated confining pressures (200–400 kPa) transformed brittle failure into ductile behavior through particle interlocking, with peak strength quadrupling under 400 kPa. SEM analysis revealed MBC stabilizes hierarchical pore networks: macropores sustain microbial activity, while mesopores are occluded by CaCO3-MBC composites, sequestering ionic byproducts to mitigate efflorescence. The optimal combination (6% MBC, 1.0 mol/L reagent, 200 kPa confinement) achieved 85% of maximum strength gain at reduced reagent cost, balancing performance and sustainability.